A Review on Augmented Reality Authoring Toolkits for Education - Dengel, Andreas; Iqbal, Muhammad Zahid; Grafe, Silke; Mangina, Eleni (Frontiers in Virtual Reality, 2022)
Creating pedagogically sound, interactive Augmented Reality experiences supporting situated and experiential learning remains a challenge to teachers without programming skills. To integrate Augmented Reality in the everyday classroom, teachers need to be capable of designing their own immersive experiences for their students, which is why an analysis of existing Authoring Toolkits is necessary to identify suitable tools for educational application development and future research directions in terms of educational Augmented Reality. We identified "easy access", "GUI-based design", and "interactive contents" as needs of teachers for designing Augmented Reality for the classroom. Based on these needs, we conducted a systematic literature review of 835 documents. Of 80 relevant articles, we included 43 peer-reviewed articles from ACM Digital Library, DBLP, IEEExplore, Scopus, Web of Science, Google Scholar, and miscellaneous other sources in our analysis. We identified 69 different Augmented Reality Authoring Toolkits and classified these with regards to their accessibility, their degree of required programming knowledge, and their interactivity. The results show a divergent research landscape with a lack of empirical evaluation. Of 26 openly accessible toolkits, we identified five openly accessible toolkits addressing the defined needs of teachers for designing interactive Augmented Reality experiences for the classroom without requiring extensive programming knowledge. We conclude that there are only few tools for the straightforward design of educational AR experiences addressing the needs of teachers and suggest using research-informed and evidence-based criteria for developing Augmented Reality Authoring Toolkits for education.